Analysis of the Welfare Level of Fisherman Households Based on the Fisherman Exchange Rate (NTN) - Muhammad_Hawlaa_Abdussalam_Shadra Shadra; Yeni Sari Wulandari; Ali Fahmi Syahputra (Grouper, 2024)
Ciparagejaya Village is one of the villages in Karawang Regency that is directly adjacent to the Java Sea waters and is dominated by fisheries activities such as capture fisheries, sea product auctions, and processing of fish caught in the sea. The existence of weather factors and moon phases can affect fishing catches which have an impact on fishermen's income, purchasing power of fishermen's households, and the level of welfare of fishermen's households. The purpose of this study is to analyze the amount of fishermen's household income from the fisheries sector which includes capture fisheries and non-fisheries and analyze the expenditure of fishermen's households which includes food and non-food expenditures, and analyze the level of welfare of fishermen's households based on the Exchange Rate of fishermen (NTN) in May 2024 in Ciparagejaya Village, Tempuran District, Karawang Regency. The method used in this research is the survey method and this research was conducted with a quantitative descriptive approach. Sampling was done purposively by involving 96 boat-owning fishermen residing in Ciparagejaya Village, Tempuran Subdistrict, Karawang Regency. This study used primary data and secondary data. Primary data was obtained through interviews using a questionnaire and secondary data was obtained through relevant agencies. The results showed that the average income from capture fisheries and non-fisheries in May 2024 amounted to Rp 2,832,158 and Rp 1,620,000. The average food and non-food expenditure of fisher households in May 2024 amounted to Rp 973,281 and Rp 713,135. The average welfare level based on the Fisherman Exchange Rate (NTN) indicator in May 2024 was 1.89. This shows that fisher households can fulfill their primary and non-primary needs.